O FEEDBACK PROCESSUAL: UMA FERRAMENTA DE CONTROLE DA NAVEGAÇÃO EM UMA APLICAÇÃO HIPERMÍDIA EDUCACIONAL - Costa, Alberto Pessoa da (2007)
The present work describes the development of an ducational hypermedia application in which it was implemented the feedback process. The feedback process is defined as a continuous feedback involving the answers of the user in contact with hypermedia application, the hypotheses that had generated these answers and the user s mental operations involved in the construction of these answers. As the center of the process in the development of educational hypermedia application is that the conception of the pedagogical mediation through the educator is indispensable in the process of teaching-learning. The situationalproblems proposals had involved the concept of speed and the co-related quantities. All the constituent elements of the definition and these which are characteristics of feedback process had been implemented successfully. It is important describe that the present work also considered as a methodology the use of the technique of storyboard in the development of educational hypermedia application. Relating to the development of educational hypermedia application it had not been done an application test as well as worrying about the amount of implemented pages. All the work was concentrated in the production of a prototype. The objective was fully reached and the prototype demonstrates clearly that the implementation of the feedback process in wide projects is viable. As a suggestion to future works it is interesting to test the prototype in class. Finally, it is expect that new efforts will be done to extend the implementation of feedback process for educational hypermedia applications focusing on other contents and in other areas of the knowledge.